Réponses

  • Omnes
  • Modérateur confirmé
2014-04-02T22:56:30+02:00
Salut,

a) 2a + 7 = 1
2a = 1 - 7
2a = -6
a = -6/2
a = -3

b) -4 = 6 + 5x
-4 - 6 = 5x
-10 = 5x
-10/5 = x
-2 = x

c) 5 - x = 8
-x = 8-5
-x = 3
x = -3

d) 5x - 8 = 3x
5x - 3x = 8
2x = 8
x = 8/2
x = 4

e) 4x = 3 - 2x
4x + 2x = 3
6x = 3
x = 3/6
x = 1/2

f) x = 4x - 6

x - 4x = -6
-3x = -6
x = -6/-3 = 2

Bonne soirée !

2014-04-03T01:02:08+02:00
Salut :)

a) 2a + 7 = 1
2a = 1 - 7
2a = -6
a = -6/2
a = -3

b) -4 = 6 + 5x
-4 - 6 = 5x
-10 = 5x
x = -10/5
x = -2

c) 5 - x = 8
-x = 8 - 5
-x  = 3
x = -3

d) 5x - 8 = 3x
-8 = 3x - 5x
-8 = -2x
x = -8/-2
x = 4

e) 4x = 3 - 2x
4x + 2x = 3
6x = 3
x = 3/6
x = 1/2
x = 0.5

f) x = 4x - 6

x - 4x = -6
-3x = -6
x = -6/-3
x = 2

J'espère t'avoir aidé(e)! :)